Peran Strategis Metode Khusus Pembelajaran PAI dalam Mengoptimalkan Pemahaman Moderasi Beragama - Ahmad Fauzi; Ferry Sopyan; Mukmin (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2025)
This study aims to examine the strategic role of special instructional methods in Islamic Religious Education (PAI) in enhancing students’ understanding of religious moderation. Using a literature review method, data were collected from various relevant scientific sources discussing PAI learning strategies and the implementation of moderation values in education. The findings indicate that interactive, dialogical, reflective, and collaborative learning methods significantly strengthen students’ understanding of the values of tawasuth (moderation), i‘tidāl (justice/balance), and tasâmuh (tolerance). The role of PAI teachers is crucial as facilitators who connect the concept of moderation with social realities and are able to adapt learning to the challenges of the digital era. However, obstacles still exist in implementing innovative methods, such as limited teacher training and the influence of social media, which may trigger intolerant attitudes. Therefore, policy support and continuous improvement of teacher competencies are necessary. In conclusion, the implementation of effective PAI learning methods can foster a moderate and inclusive religious attitude, thereby encouraging the creation of harmony within a pluralistic society.